Collateral sensitivity constrains resistance evolution of the CTX-M-15 β-lactamase - Carola E. H. Rosenkilde (Nature Portfolio, 2019)
Development of bacterial resistance to an antibiotic can lead to collateral sensitivity to another drug. Here, the authors study collateral sensitivity conferred by mutations in the horizontally acquired β-lactamase CTX-M-15, and identify antibiotic combinations that constrain the evolution of resistance.